POLA PENGASUHAN DAN PENINGKATAN ASPEK PERKEMBANGAN PENGETAHUAN MORAL MELALUI GERAK DAN LAGU PADA ANAK USIA DINI - Dhaifi, Ilzam; Putri, Yayuk (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Moral development needs to be instilled from an early age, including awareness of gender differences. Moral instillation in children will hopefully have implications for their awareness and sensitivity about pro-social conditions that must be built properly. One of the actions of instilling moral education through music activities is movement and the song